One-step in situ synthesis of NHx-adsorbed rhodium nanocrystals at liquid-liquid interfaces for possible electrocatalytic applications - Patil, V. S.; Krishna, S. R.; Hawaldar, Ranjit R.; Gaikwad, A. B.; Sathaye, S. D.; Patil, K. R. (Journal of Colloid and Interface Science, 2011)
Nearly monodisperse rhodium nanoparticles with adsorbed NHx were synthesized at the CCl4-water interface. The presence of NHx-adsorbed species was confirmed by energy-dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS) studies. The synthesis of controlled size 2-38 nm rhodium particles was studied as a function of reducing agent concentration by transmission electron microscopy (TEM). HRTEM confirmed the formation of rhodium nanoparticles having fringe spacing consistent with reported Rh (1 1 1) planes. The continuity of these films over an area of 1 x 1 pm was revealed by atomic force microscopy (AFM) studies. The electrocatalytic application of these nanostructure Rh-NHx), thin films for formaldehyde oxidation in 0.5 M NaOH was investigated by cyclic voltammetry. The Rh nanoparticles formed by the present strategy are expected to be useful for other catalytic applications also. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrazine hydrate; Liquid-liquid interface; Nanoparticles; Rhodium; Thin films